2019
DOI: 10.1109/jphot.2019.2910847
|View full text |Cite
|
Sign up to set email alerts
|

All-Fiber Multiplexing and Transmission of High-Order Circularly Polarized Orbital Angular Momentum Modes With Mode Selective Couplers

Abstract: We have demonstrated an all-fiber high-order circularly polarized (CP) orbital angular momentum (OAM) modes (de)multiplexing system based on second-order mode selective couplers (SMSCs). Such SMSCs combining standard single mode fiber and ring core fiber (RCF) are fabricated by a fusing and pulling technique, in which the RCF supports second-order vector modes (HE 31 and EH 11). During a pulling process, the HE 31 and EH 11 modes could be excited along the coupling region through evanescent wave interaction. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Wen et al 141 reported amplification of OAM modes generated using fused couplers, which have an 160-nm bandwidth (1480 to 1640 nm). This technique was further scaled for exciting the higher-order circularly polarized OAM modes ðl ¼ AE2Þ using a ring core fiber, 142 and a modal power extinction ratio of 12.9 dB was reported with respect to the neighboring modes. The fused coupler technique is employed in making mode-selective photonic lanterns (MSPLs) exciting five OAM modes in a ring core fiber with a bandwidth of 500 nm (1000 to 1500 nm).…”
Section: Hybrid Approachmentioning
confidence: 99%
“…Wen et al 141 reported amplification of OAM modes generated using fused couplers, which have an 160-nm bandwidth (1480 to 1640 nm). This technique was further scaled for exciting the higher-order circularly polarized OAM modes ðl ¼ AE2Þ using a ring core fiber, 142 and a modal power extinction ratio of 12.9 dB was reported with respect to the neighboring modes. The fused coupler technique is employed in making mode-selective photonic lanterns (MSPLs) exciting five OAM modes in a ring core fiber with a bandwidth of 500 nm (1000 to 1500 nm).…”
Section: Hybrid Approachmentioning
confidence: 99%
“…underwater wireless optical communication [9] and optical fiber communication [10]. At present, there are two mainly generation methods of OAM modes, free space-based and optical fiber-based methods, including spatial light modulators [11,12], fiber gratings [13,14], helical long-period fiber grating [15,16] and mode selective couplers (MSCs) [17][18][19][20][21]. Among these methods, MSC can be considered valuable due to the virtue of low loss, small size, and easy to couple with fibers.…”
Section: Introductionmentioning
confidence: 99%